MENGIDENTIFIKASI DAN MENGEMBANGKAN KEMAMPUAN PENALARAN STATISTIS - Habibi Ratu Perwira Negara; Farah Heniati Santosa; Malik Ibrahim (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this paper is in the form of a literature study of the ability of statistical reasoning. The study was conducted on the understanding of statistical reasoning abilities, identifying and developing statistical reasoning abilities by tracing the opinions of experts as well as related research results about developing statistical reasoning abilities in the learning process. The study was conducted by tracking the results of research on the ability of statistical reasoning, both national and international research results.Keywords: Statistics, Statistics, statistical reasoning.